Critical success factors of knowledge management implementation in higher learning institutions. (23rd April 2019) - Yip, Mum Wai; Ng, Alex Hou Hong
The main purpose of this study is to examine the relationship between the soft elements of critical success factors and perceived benefits of knowledge management (KM) in higher learning institutions which can lead to the development of the KM model for higher learning institutions. The outcomes of this study revealed that organisational culture and top management leadership have a positive relationship with the perceived benefits of KM. Nevertheless, education and training has a negative relationship with the perceived benefits of KM. On the other hand, the employee participation and empowerment through teamwork did not show any relationship with the perceived benefits of KM. The major findings of the study conclude that organisational culture and top management support have a positive relationship with perceived benefits of KM, while the opposite is true for employee participation and empowerment. In conclusion, organisations need to cultivate the right culture and leadership to embrace KM.